Use of eHealth as a Complement in the Care Provided to Patients in Chemotherapy Treatment - Magalhães, Bruno (2021)
We are witnessing a new technological era in oncology related to: the management of  signs and symptoms, the surveillance of complications associated with treatments, the process of follow-up by monitoring the adherence to therapy, and even the way we communicate or interact with patients, healthcare professionals and hospital institutions. Mobile technology (mHealth) is being increasingly used as an efficient strategy to improve adherence to therapy, and it can also be a viable  resource for health education, guiding interventions, allowing professionals to monitoring toxicities or behaviors and providing self-care guidelines for the user, namely cancer patients, undergoing chemotherapy. The advances of mHealth technology enable a new era in oncology care. However, it is important to reflect on its implications for clinical practice and research. And to recognize the  limitations that these technologies may have, namely in terms of their design.   There is still a long way to go to make these resources valid, safe and accessible to users. It is necessary that the applications evolve beyond the academic scenario (in which most of them are develop) and increase their use in clinical practice, thus allowing a true assessment of the impact of this “new” intervention modality in oncology.